Experimental-numerical simulation of soluble formations in reservoirs. (February 2022) - Tavoosi, Negar; Hooshyaripor, Farhad; Noori, Roohollah; Farokhnia, Ashkan; Maghrebi, Mohsen; Kløve, Bjørn; Haghighi, Ali Torabi
Highlights: Gypsum rocks in parsian reservoir enhances risk of water quality degradation. Dissolution rate was estimated between 0.023 and 0.056 gr/cm 2 -day through experiments. The reservoir salinization was modeled by CE-QUAL-W2 under different scenarios. Dissolution could enhance the average TDS of the dam outflow from 1429 to 1722 mg/L. Omitting a saline inflow river at upstream reduces TDS in outflow to 900 mg/L. Abstract: Saline inflows and soluble geological formations outcropped in reservoirs contribute to reservoir water salinization (RWS). We set up 32 laboratory tests to better understand rock-water interaction and determination of dissolution rate of Gachsaran geological formation (GGF) in the Parsian dam that is currently under the study phase on the Fahlian river, Iran. Then, we used CE-QUAL-W2 (W2) to simulate GGF dissolution outcropped in some parts of the reservoir. Finally, possible solutions for mitigating the RWS were investigated using W2 driven under different scenarios: (1) having Hamze-beigi saline inflow (a main tributary of the Fahlian river) and GGF dissolution, (2) removing the saline inflow, (3) confining the GGF dissolution, and (4) driving W2 in severe floods. Although the dissolution rates (0.023–0.056 gr/cm 2 -day) salinize deep water, saline inflow degrades surface waters. Density gradient in the water depth formed the monimolimnion and mixolimnion separated by a distinct pycnocline in the reservoir. The pycnocline established in the early impoundment stage and lasted throughout the study period (2002–2012), leading to a crenogenic meromixis state in the reservoir. W2 driven under the 100–year and 1000–year inflows shows salinity up to 2700 mg/L in top layers from partial chemical mixing in the reservoir in cold months, although no conversion of the lake from the meromixis to holomictic state was observed in warm months. The findings suggest that, although diversion of the saline inflow satisfies the salinity requirement for hydropower generation, peak saline inflow can salinize the reservoir water and downstream river.